1986
DOI: 10.2307/1958273
|View full text |Cite
|
Sign up to set email alerts
|

The President and the Political Use of Force

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.T hroughout the post-World War II period the president has been called upon to make decisions concerning the use of force as a political instrument. The explanation that is offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
407
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(413 citation statements)
references
References 16 publications
(13 reference statements)
4
407
1
1
Order By: Relevance
“…Some scholars have suggested that this dynamic should apply primarily to democratic leaders because of their dependence on public support for maintaining office and because of their inability to use more direct methods of dampening domestic dissent (Richards et al 1993, Downs & Rocke 1995, Gelpi 1997. Consistent with this expectation, several studies of American foreign policy indicate that presidents have been more likely to use military force when their approval ratings have been in decline (Ostrom & Job 1986, James & Oneal 1991, Fordham 1998. Other studies have indicated-contrary to the diversionary logic-that U.S. presidents have been more likely to use military force when economic conditions have been favorable (Lian & Oneal 1993, Meernik & Waterman 1996.…”
mentioning
confidence: 95%
“…Some scholars have suggested that this dynamic should apply primarily to democratic leaders because of their dependence on public support for maintaining office and because of their inability to use more direct methods of dampening domestic dissent (Richards et al 1993, Downs & Rocke 1995, Gelpi 1997. Consistent with this expectation, several studies of American foreign policy indicate that presidents have been more likely to use military force when their approval ratings have been in decline (Ostrom & Job 1986, James & Oneal 1991, Fordham 1998. Other studies have indicated-contrary to the diversionary logic-that U.S. presidents have been more likely to use military force when economic conditions have been favorable (Lian & Oneal 1993, Meernik & Waterman 1996.…”
mentioning
confidence: 95%
“…And Russett's (1990b) efforts similarly support the claim that US dispute involvement is negatively related to economic activity. Ostrom and Job (1986) review biannual, post-WWII data for the United States and find that the propensity to use major force is significantly related to an ''economic misery'' index. But many of these studies and their underlying empirics have been heavily criticized.…”
Section: Diversionary Expectationsmentioning
confidence: 99%
“…It also decreases transnational terrorism. According to Levy (1989), Meernik, Krueger, and Poe (1998), Meernik and Waterman (1996), Ostrom and Job (1986), Rummel (1963) and Smith (1996), belligerent politicians use wars as a diversionary tactic to consolidate their domestic position in domestic crises. These scholars hold that unpopular democratic governments can use active foreign policy (diversionary war) to win electoral support but there is no evidence that such a policy leads to re-election or the realization of strategic objectives.…”
Section: Conflict-aid Nexusmentioning
confidence: 99%
“…Meernik and Waterman (1996), Ostrom and Job (1986) and Wilkenfeld (1968) find that the decision to start war is determined by the nature of regime (polyarchic or authoritarian), international political issues and domestic concerns. Meernik and Waterman (1996) find little evidence that domestic conditions, trade and domestic support determine the use of force.…”
Section: Conflict-aid Nexusmentioning
confidence: 99%